White Matter Plasticity Keeps the Brain in Tune: Axons Conduct While Glia Wrap - Chorghay, Zahraa; Káradóttir, Ragnhildur Thóra; Ruthazer, Edward S. (Frontiers in Cellular Neuroscience, 2018)
Precise timing of neuronal inputs is crucial for brain circuit function and development, where it contributes critically to experience-dependent plasticity. Myelination therefore provides an important adaptation mechanism for vertebrate circuits. Despite its importance to circuit activity, the interplay between neuronal activity and myelination has yet to be fully elucidated. In recent years, significant attention has been devoted to uncovering and explaining the phenomenon of white matter plasticity. Here, we summarize some of the critical evidence for modulation of the white matter by neuronal activity, ranging from human diffusion tensor imaging studies to experiments in animal models. These experiments reveal activity-dependent changes in the differentiation and proliferation of the oligodendrocyte lineage, and in the critical properties of the myelin sheaths. We discuss the implications of such changes for synaptic function and plasticity, and present the underlying mechanisms of neuron-glia communication, with a focus on glutamatergic signalling and the axomyelinic synapse. Finally, we examine evidence that myelin plasticity may be subject to critical periods. Taken together, the present review aims to provide insights into myelination in the context of brain circuit formation and function, emphasizing the bidirectional interplay between neurons and myelinating glial cells to better inform future investigations of nervous system plasticity.